Analisis Pengaruh Masukan Udara pada Ruang Bakar Boiler Pipa Api Kapasitas 100 Kg/ Jam untuk Meningkatkan Efisiensi Energi - Gafur, Abdul; Zulkarnain, Zulkarnain; Sunarto, Sunarto; Syafika, Nurul (Jurnal Mekanik Terapan, 2025)
This study aims to improve the energy efficiency of a 100 kg/h fire-tube mini boiler through combustion chamber redesign and analysis of air intake variations. The redesign was conducted using SolidWorks software with thermal insulation made of bricks, cement, sand, and refractory cement to reduce heat loss. Experiments were carried out by varying blower air velocity from 3 to 17 m/s, measuring combustion chamber temperature, steam temperature, water temperature, pressure, fuel consumption, and energy efficiency. The results show that an air velocity of 11 m/s achieved the best performance, with a maximum efficiency of 86% at 1 bar pressure. Efficiency decreased at lower air velocity due to limited oxygen supply and at higher velocity due to excessive air absorbing heat energy. The redesigned combustion chamber produced more stable combustion, reduced fuel consumption, and improved continuous steam production